2004
DOI: 10.1177/1359104504043916
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioner Perceptions and Practice Related to Adolescent Depressive Presentations

Abstract: A B S T R A C TRecognizing that child and adolescent psychiatry operates in the context of opinions, we set out to discover GPs' views and prescribing practices in connection to adolescent depressive presentations. Two-thirds of respondents felt there had been a recent increase in presentations and their views on the reasons were further examined. However, only one third have been prescribing more often and the reasons for this were also examined. It is clear that although they recognize increased unhappiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…There are a number of reasons why GPs might not readily adopt this new role. Although GPs believe that depressive presentations among teenagers are becoming increasingly common (Vandana and Ambelas, 2004) and do identify most of those with severe psychological morbidity, they also fail to identify the majority of those with depressive disorders (Angold et al ., 1999). There is some evidence that GPs spend less time in consultation with young people (Jacobson et al ., 2002) and many practitioners feel that teenagers are hard to communicate with and worry about over-medicalizing their lives (MacFarlane and McPherson, 1995; Iliffe et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of reasons why GPs might not readily adopt this new role. Although GPs believe that depressive presentations among teenagers are becoming increasingly common (Vandana and Ambelas, 2004) and do identify most of those with severe psychological morbidity, they also fail to identify the majority of those with depressive disorders (Angold et al ., 1999). There is some evidence that GPs spend less time in consultation with young people (Jacobson et al ., 2002) and many practitioners feel that teenagers are hard to communicate with and worry about over-medicalizing their lives (MacFarlane and McPherson, 1995; Iliffe et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although GPs believe that depression is becoming increasingly common among teenagers 12 and do identify and react to most of those with severe psychological morbidity, they also fail to identify the majority of those with depressive disorders. 9 There is some evidence that GPs spend less time in consultations with young people; 10 some practitioners feel that teenagers are hard to communicate with and worry about overmedicalising their lives.…”
mentioning
confidence: 99%
“…At present, there is significant variation in the abilities of primary care providers to effectively identify and manage mental health problems. In a recent issue of CCPP, Vandana and Ambelas (2004) found that GPs appear to recognize increased unhappiness among adolescents, yet they are hesitant to diagnose and treat depressive presentations. How can this be best accomplished?…”
Section: Arlene Vetere and The Countless Others Who Have Shaped My Tmentioning
confidence: 98%